2023
DOI: 10.1002/smll.202304047
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Hydrogels: Potential Materials for Medical Application

Yanni Li,
Yujia Han,
Hongxia Li
et al.

Abstract: Microbial infections based on drug‐resistant pathogenic organisms following surgery or trauma and uncontrolled bleeding are the main causes of increased mortality from trauma worldwide. The prevalence of drug‐resistant pathogens has led to a significant increase in medical costs and poses a great threat to the normal life of people. This is an important issue in the field of biomedicine, and the emergence of new antimicrobial materials hydrogels holds great promise for solving this problem. Hydrogel is an impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 274 publications
0
13
0
Order By: Relevance
“…First, the absorber should possess the impedance matching property, enabling the entry of the EMW with low reflection. 51 Second, the absorber must exhibit efficient attenuation characteristics, resulting in the effective dissipation of electromagnetic energy. 21 The impedance matching and attenuation constant can be calculated as follows: 52 Zr…”
Section: Emw Absorption Mechanismmentioning
confidence: 99%
“…First, the absorber should possess the impedance matching property, enabling the entry of the EMW with low reflection. 51 Second, the absorber must exhibit efficient attenuation characteristics, resulting in the effective dissipation of electromagnetic energy. 21 The impedance matching and attenuation constant can be calculated as follows: 52 Zr…”
Section: Emw Absorption Mechanismmentioning
confidence: 99%
“…Hydrogels are soft-solid materials with a cross-linked three-dimensional polymer network. Owing to their high hydrophilic properties and unique structures, hydrogels have been widely applied in drug delivery, wound healing, tissue engineering scaffolds, and cosmetics. Injectable hydrogels with superior functional properties are promising biomaterials for soft tissue augmentation due to their simple application procedures and low costs. , Under shear stress, the viscosity of hydrogels decreases significantly, enabling the injectability as a liquid. Subsequently, injectable hydrogels recover their original network structure and mechanical strength.…”
Section: Introductionmentioning
confidence: 99%
“…43 The preparation methods for the binding of antimicrobial agents to hydrogels mainly include physical binding (direct encapsulation, solubilization and diffusion, carrier encapsulation) and chemical binding (formation of chemical bonds between hydrogels with inherent antimicrobial activity). 40,44 Amines are widely present in the biological world, with very important physiological and biological activities; for example, alkaloids, nucleic acids, antibiotics, and proteins are amine derivatives, and most of the drugs are amines or amine derivatives, so mastering the nature and synthesis of amines is the basis of the study of these complex natural products and the better maintenance of human health. 45,46 Dimethylammonium ethyl methacrylate (DM) is amine basic; the molecule contains a tertiary amino group, an ester group, and an unsaturated double bond, and acid can produce salt and chloromethane and other reactions to produce quaternary ammonium ionic liquids (DM x ).…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, the emergence of antimicrobial materials offers great hope for solving the problem of infection risk. For example, cationic polyelectrolyte brushes grafted from bacterial cellulose (BC) nanofibers were introduced into a polydopamine/polyacrylamide hydrogel by Yang et al, and the hydrogel showed less inflammatory response and a faster healing rate in wound healing in rats in vivo . The preparation methods for the binding of antimicrobial agents to hydrogels mainly include physical binding (direct encapsulation, solubilization and diffusion, carrier encapsulation) and chemical binding (formation of chemical bonds between hydrogels with inherent antimicrobial activity). , Amines are widely present in the biological world, with very important physiological and biological activities; for example, alkaloids, nucleic acids, antibiotics, and proteins are amine derivatives, and most of the drugs are amines or amine derivatives, so mastering the nature and synthesis of amines is the basis of the study of these complex natural products and the better maintenance of human health. , Dimethylammonium ethyl methacrylate (DM) is amine basic; the molecule contains a tertiary amino group, an ester group, and an unsaturated double bond, and acid can produce salt and chloromethane and other reactions to produce quaternary ammonium ionic liquids (DM x ). , Taking inspiration from the alkylamines in the natural antibacterial purple daisy, we synthesized a series of antibacterial hydrogels based on DM x ( X = 2, 6, 12, and 16) with different chain lengths. The effect of the length of the hydrophobic alkyl group on the antimicrobial activity of DM x and on the mechanical properties of the aniline sphere-toughened hydrogel as well as the effect of the aniline sphere content on the conductivity of the hydrogel were investigated in more detail.…”
Section: Introductionmentioning
confidence: 99%